Global Trade Watch 2017 : Trade Defies Policy Uncertainty–Will It Last? - Constantinescu, Cristina; Mattoo, Aaditya; Mulabdic, Alen; Ruta, Michele (World Bank, Washington, DC, 2018)
Trade rebounded in 2017, with trade volume growing at 4.3 percent in 2017—the fastest rate in 6 years. The recovery of trade is not limited to a few regions but is widespread, suggesting that we may be at a turning point. The largest contributions to global trade growth have come from East Asian countries in the developing world and the Euro area in the developed world. Merchandise trade, which in recent years has been less resilient than services trade, picked up, growing by 4.5 percent in 2017. Cyclical factors drove better trade performance in 2017. Trade grew faster because real gross domestic product grew faster. Investment growth played a critical role because investment is the most import intensive component of aggregate demand, and capital goods production has longer global value chains (GVCs). Preliminary monthly data indicate that the import values of capital goods such as machinery and electrical equipment grew in 2017 at the fastest rates since 2012 and that they have been the most significant contributors to 2017 nonfuel import growth in the European Union and United States. The improved performance of trade may be widespread, but it is fragile. Some of the factors underlying the global trade slowdown of recent years—weak growth in GVCs and high trade policy uncertainty—are still present. In particular, there are serious risks in the trade policy domain. The share of merchandise trade that trade-restrictive measures cover remained stable at approximately 1 percent in 2017. But the portion due to trade remedy initiations—a harbinger of future protection — has increased significantly since 2015, and there are risks of policy reversals in major markets. At the same time, new deep trade agreements have recently entered into force and others are being negotiated.